Entrepreneurial practices and new managerial technologies in undergraduate nursing education (Research, Society and Development, 2022)
To report the experience of professors in teaching entrepreneurship and new technologies in nursing. This is an account of the experience of professors at a University Center in the interior of Pernambuco, developed in the Thematic Unit (UT) 20 “Nursing Work Process at the Secondary and Tertiary Levels of Health and Entrepreneurial Practices”. The experience took place in the second half of 2019, in which 02 professors and 22 students participated in the activities. The first stage of the teaching process started with theoretical and discursive classes. Then, a technical visit was carried out, which aimed to elucidate, in practice, the reality of management in the various interfaces of hospital operation. The third stage of teaching materialized in the construction of the company from idea workshops. It is considered that this pedagogical methodology needs to be disseminated in the curricular structures of undergraduate nursing courses.